2012
DOI: 10.1111/j.1600-0609.2012.01785.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐specific analysis of FLT3 internal tandem duplications for the prognostication and monitoring of acute myeloid leukemia

Abstract: Objectives Internal tandem duplications (ITDs) of the fms‐like tyrosine kinase 3 ( FLT3) gene occur in 13–35% of patients with acute myeloid leukemia (AML). FLT3‐ITD is associated with poor clinical outcome and is an indication for allogeneic stem cell transplantation (allo‐SCT). Methods To investigate FLT3‐ITD length, position, and mutational load in AML cases, we developed patient‐specific quantitative real‐time reverse transcription polymerase chain reaction (qRT‐PCR) assays and correlated the results wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…20,21 Using FLT3 mutation as an MRD marker has not been standardized or demonstrated in large studies; however, several small studies have suggested that FLT3 mutations may be useful as an MRD marker, especially when sensitive methods are employed. [22][23][24][25] In our limited numbers, FLT3-ITD mutations was negative in all tested patients while some of them had residual disease by other meth- …”
mentioning
confidence: 63%
“…20,21 Using FLT3 mutation as an MRD marker has not been standardized or demonstrated in large studies; however, several small studies have suggested that FLT3 mutations may be useful as an MRD marker, especially when sensitive methods are employed. [22][23][24][25] In our limited numbers, FLT3-ITD mutations was negative in all tested patients while some of them had residual disease by other meth- …”
mentioning
confidence: 63%
“…Patients with FLT3-TKD mutations on D835 indeed had a reduced response to these two drugs (48,97). Furthermore, within patients containing FLT3-ITD mutations, the location and length of ITD also affect the sensitivity to FLT3 inhibitor treatment of FLT3 inhibitors (32,33,98,99). Patients with ITD reaching to the TKD away from the JM domain are known to have a poor prognosis for the induction chemotherapy (32,33).…”
Section: Inherent Mechanismsmentioning
confidence: 99%
“…Whereas NPM1 has been shown to be a reliable marker for minimal residual disease patient-specific primers, aim to improve the sensitivity of FLT3-ITD. 67 However, this approach has limitations, since each FLT3-ITD mutation needs a clone-specific primer/probe set, which is time-consuming and may not be possible in every case. In addition, direct sequencing may not be possible in patients with a low allelic ratio since the wild-type sequence is competitively amplified.…”
Section: Detection Of Minimal Residual Diseasementioning
confidence: 99%